Physical fitness and performance of Polish ice-hockey players competing at different sports levels - Roczniok, R.; Stanula, A.; Gabrys, T.; Szmatlan-Gabrys, U.; Golas, A.; Stastny, P. (Journal of Human Kinetics, 2016)
The study aimed to determine the values of selected aerobic and anaerobic capacity variables, physical profiles, and to analyze the results of on-ice tests performed by ice-hockey players relegated to a lower league. Performance of 24 ice-hockey players competing in the top league in the 2012/2013 season was analysed to this end. In the 2013/2014 season, 14 of them still played in the top league (the control group), while 10 played in the first league (the experimental group). The study was conducted one week after the end of the playoffs in the seasons under consideration. The results revealed that only in the experimental group the analysed variables changed significantly between the seasons. In the Wingate test, significant changes were only noted in mean relative power (a decrease from 9.91 to 9.14 W/kg; p=0.045) and relative total work (a decrease from 299.17 to 277.22 J/kg; p=0.048). The ramp test indicated significantly lower power output in its final stages (364 compared with 384 W; p=0.034), as well as a significant decrease in relative VO2max (from 52.70 to 48.30 ml/min/kg). Blood lactate concentrations were recorded at the 3rd, 6th, 9th and 12th min of recovery after the ramp test. The rate of post-exercise recovery, LA, recorded after the ramp test turned out to be significantly lower. The times recorded in the on-ice "6x30 m stop" test increased from 32.18 to 33.10 s (p=0.047). The study showed that playing in a lower league where games were less intensive, training sessions shorter and less frequent, had an adverse effect on the performance level of the investigated players. Lower VO2max recorded in the study participants slowed down their rates of post-exercise recovery and led to a significantly worse performance in the 6x30 m stop test, as well as lower relative power and relative total work in the Wingate test.